Zooplankton biomass and metabolism in the frontal zones of the Bransfield Strait, Antarctica - Hernández-León, S.; Sangrá Inciarte, Pablo; Lehette, P.; Lubián, L.; Almeida, C.; Putzeys, S.; Bécognée, P.; Andrade, M.P. (Journal of Marine Systems, 2013)
Biomass, abundance, gut fluorescence and electron transfer system (ETS) activity of zooplankton have been studied in the Bransfield Strait (Antarctic Peninsula). Two well-defined frontal systems were observed: (1) the so-called Peninsula front between the Transitional Bellingshausen Water (TBW) and Transitional Weddell Waters (TWW); and (2) the Bransfield front related to the Bransfield Gravity Current flowing northeastward along the slope of the South Shetland Islands. As expected, a typical pattern of plankton distribution was observed with higher phyto- and mesozooplankton in the TBW. However, our more detailed study of the Peninsula front between the TBW and TWW showed the sinking of phytoplankton and a higher abundance of large copepods on the TBW side of the front, while krill and small copepods were observed on the opposite side, in the TWW. Ageostrophic secondary circulation around the front supported a striking food web at both sides of the front. It is suggested that this pattern drives a relatively important flux of carbon, due to the sinking of phytoplankton and the production of fast sinking fecal pellets by large copepods and krill.